Robust Switching Gain-Based Fractional-Order Sliding Mode Control for Wind-Powered Microgrids - Minghao Zhou; Siwei Cheng; Long Xu; Likun Wang; Qingbo Guo; William Cai (Complexity)
This study proposes a novel fractional-order sliding-mode control strategy with robust switching gain to achieve reliable and high quality of wind-powered microgrid systems. Three fractional-order sliding mode controllers are designed to generate continuous control signals and regulate the outer DC-link voltage loop and inner current loop in the grid-side inverters. High robustness and stability of the grid-side inverter can be guaranteed even in the presence of parameter variations and external disturbances. Owing to the fractional-order sliding manifold and fractional-order integral control law, the chattering is attenuated. The fractional-order robust adaptive switching gain is designed to avoid overestimating the upper bound of matched/unmatched uncertainties, save the control energy, and guarantee the rapidity and robustness of the convergence. Simulations validate the proposed method.